Nicotinamide riboside supplementation alters body composition and skeletal muscle acetylcarnitine concentrations in healthy obese humans - Remie, Carlijn M E; Roumans, Kay H M; Moonen, Michiel P B; Connell, Niels J; Havekes, Bas; Mevenkamp, Julian; Lindeboom, Lucas; de Wit, Vera H W; van de Weijer, Tineke; Aarts, Suzanne A B M; Lutgens, Esther; Schomakers, Bauke V; et al. (The American journal of clinical nutrition, 2020)
ABSTRACT Background Nicotinamide riboside (NR) is an NAD+ precursor that boosts cellular NAD+ concentrations. Preclinical studies have shown profound metabolic health effects after NR supplementation. Objectives We aimed to investigate the effects of 6 wk NR supplementation on insulin sensitivity, mitochondrial function, and other metabolic health parameters in overweight and obese volunteers. Methods A randomized, double-blinded, placebo-controlled, crossover intervention study was conducted in 13 healthy overweight or obese men and women. Participants received 6 wk NR (1000 mg/d) and placebo supplementation, followed by broad metabolic phenotyping, including hyperinsulinemic-euglycemic clamps, magnetic resonance spectroscopy, muscle biopsies, and assessment of ex vivo mitochondrial function and in vivo energy metabolism. Results Markers of increased NAD+ synthesis—nicotinic acid adenine dinucleotide and methyl nicotinamide—were elevated in skeletal muscle after NR compared with placebo. NR increased body fat-free mass (62.65% ± 2.49% compared with 61.32% ± 2.58% in NR and placebo, respectively; change: 1.34% ± 0.50%, P = 0.02) and increased sleeping metabolic rate. Interestingly, acetylcarnitine concentrations in skeletal muscle were increased upon NR (4558 ± 749 compared with 3025 ± 316 pmol/mg dry weight in NR and placebo, respectively; change: 1533 ± 683 pmol/mg dry weight, P = 0.04) and the capacity to form acetylcarnitine upon exercise was higher in NR than in placebo (2.99 ± 0.30 compared with 2.40 ± 0.33 mmol/kg wet weight; change: 0.53 ± 0.21 mmol/kg wet weight, P = 0.01). However, no effects of NR were found on insulin sensitivity, mitochondrial function, hepatic and intramyocellular lipid accumulation, cardiac energy status, cardiac ejection fraction, ambulatory blood pressure, plasma markers of inflammation, or energy metabolism. Conclusions NR supplementation of 1000 mg/d for 6 wk in healthy overweight or obese men and women increased skeletal muscle NAD+ metabolites, affected skeletal muscle acetylcarnitine metabolism, and induced minor changes in body composition and sleeping metabolic rate. However, no other metabolic health effects were observed. This trial was registered at clinicaltrials.gov as NCT02835664